2021
DOI: 10.1002/cre2.512
|View full text |Cite
|
Sign up to set email alerts
|

A novel drug delivery system using acyclovir nanofiber patch for topical treatment of recurrent herpes labialis: A randomized clinical trial

Abstract: Objectives: Topical treatment with acyclovir cream has shown low efficacy in recent studies. Nano drug delivery systems, have received much attention in recent decades.The aim of this study was to compare the efficacy of acyclovir nanofiber patch with acyclovir cream.Material and Methods: In this double-blind three-armed randomized clinical trial, a total of 60 patients with recurrent labial herpes, were randomly divided into three groups, each consisting of 20. The patients in the first, second, and third gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Only small (molecular weight <500 Daltons), soluble (usually low melting point) and moderately lipophilic (log P value between 0-5) compounds with few hydrogen bonds easily pass SC unless some form of skin penetration enhancement technology is used. A larger and more lipophilic drug has more difficulty in passing into the more hydrated living epidermis due to its poor water solubility 27, 28 . Due to the disadvantages of conventional formulations, exploration of potential applications of new carriers such as vesicles, lipidic particles and nano-sized carriers has become an integral part of the development of topical skin disease therapy 8 .…”
Section: Topical Drug Carrier Systemsmentioning
confidence: 99%
“…Only small (molecular weight <500 Daltons), soluble (usually low melting point) and moderately lipophilic (log P value between 0-5) compounds with few hydrogen bonds easily pass SC unless some form of skin penetration enhancement technology is used. A larger and more lipophilic drug has more difficulty in passing into the more hydrated living epidermis due to its poor water solubility 27, 28 . Due to the disadvantages of conventional formulations, exploration of potential applications of new carriers such as vesicles, lipidic particles and nano-sized carriers has become an integral part of the development of topical skin disease therapy 8 .…”
Section: Topical Drug Carrier Systemsmentioning
confidence: 99%
“…However, the prepared product had relatively low potential performance compared to commercial Zovirax cream (5% w / w ) [ 9 ]. Therefore, a double blind randomized clinical trial was conducted to compare the therapeutic efficacy of ACV cream and ACV-loaded nanofiber patch to treat recurrent labia herpes (60 patients in three groups) [ 10 ]. The product was not substantially effective to shorten crusting time and healing time among all groups tested.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, nanofiber-based products used in medicine field involve filtering devices, surgical implants and wound dressings and patches developed for drug delivery [ 5 ]. Recent randomized clinical trial (60 patients) concerning the use of acyclovir NF patch for topical treatment of recurrent herpes labialis concluded that although NF patch accelerates symptom relief it is ineffective in shortening healing time [ 8 ].…”
Section: Introductionmentioning
confidence: 99%